2007
DOI: 10.1364/oe.15.004795
|View full text |Cite
|
Sign up to set email alerts
|

Coupling in dual-core photonic bandgap fibers: theory and experiment

Abstract: We have theoretically and experimentally investigated dual-core photonic bandgap fibers (PBGFs), which consist of a cladding with an array of high-index rods and two cores formed by omitting two nearby rods. We find novel features in their coupling characteristics such as maxima and minima in coupling length, complete decoupling of the cores, and an inversion of the usual ordering of supermodes so that the odd supermode has the higher propagation constant. This behavior is understood by considering the field d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(44 citation statements)
references
References 16 publications
0
43
1
Order By: Relevance
“…Couplers in photonic bandgap guiding fibers behave similarly for low frequencies inside the bandgap, however, the coupling length does not always increase monotonically with frequency, and can be modified by coupling to high-index inclusions [28], [31]. A microanalyte channel placed between two bandgap guiding cores can therefore be expected to have a strong influence on the coupling between the cores, and hence the transmittance of the coupler at any given wavelength.…”
Section: B Principle Of Operationmentioning
confidence: 99%
“…Couplers in photonic bandgap guiding fibers behave similarly for low frequencies inside the bandgap, however, the coupling length does not always increase monotonically with frequency, and can be modified by coupling to high-index inclusions [28], [31]. A microanalyte channel placed between two bandgap guiding cores can therefore be expected to have a strong influence on the coupling between the cores, and hence the transmittance of the coupler at any given wavelength.…”
Section: B Principle Of Operationmentioning
confidence: 99%
“…Theoretical and experimental studies of multi-core PBGFs have shown that such fibers have some remarkable coupling properties, e.g. the decoupling and extremes of coupling length [4,5]. Here we describe a novel PBGFs with two solid cores and one single microfluidic analyte channel between two cores.…”
Section: Introductionmentioning
confidence: 98%
“…The practical detection limit of fiber sensor is bottlenecked by 10 -5 RIU [1,2,3]. Meanwhile, we witness that, due to the flexibility of design and ease of fabrication, multi-core PCFs, especially the multi-core PBGFs, have attracted increasing interests for potential applications of optical communication and sensors [4,5,6]. Theoretical and experimental studies of multi-core PBGFs have shown that such fibers have some remarkable coupling properties, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, photonic crystal fibers (PCFs) have received considerable attention recently, as PCF allows infiltration of the analyte into the air holes, thereby maximizing the interaction between the probing electromagnetic field and ambient analyte [1,2,3]. Furthermore, due to the flexibility of design and ease of fabrication, multi-core PCF is advantageous for applications in optical communication and sensing [4,5,6]. However, fiber sensors based on either conventional single mode fiber (SMF) or PCFs currently cannot compete with some other photonic sensors, e.g., surface plasmon resonance (SPR) sensors.…”
Section: Introductionmentioning
confidence: 99%